Factors influencing positive perceptions of hybrid teaching in higher education: a case study of an engineering university - Li, Qiong; Xie, Rongrong; Li, Minhui (International Journal of Educational Technology in Higher Education, 2025)
As technology has advanced, blended online and offline teaching has gradually emerged as the predominant mode of instruction in higher education. This integrated, hybrid teaching model creates more complex teaching and learning scenarios than encountered in traditional classroom teaching. This study employed a mixed-methods approach to investigate the factors within the teaching, learning, and assistant teaching fields that influence perceptions of hybrid teaching in the context of higher engineering education. Initially, the foundational framework for this research was established based on Bourdieu’s field theory. A total of 550 questionnaires were distributed, and 489 valid responses were received. The quantitative analysis conducted for this research used correlation analysis, multiple linear regression, and structural equation modelling. Subsequently, qualitative interviews were conducted with teachers, students, and technical support staff. The results indicate that the teaching field significantly influences overall positive perceptions of hybrid teaching, in which context social capital and symbolic capital play crucial roles. Although the learning field does not directly impact perceptions of hybrid teaching, it enhances students’ engagement and learning opportunities. The assistant teaching field, which is characterized by the support of technical personnel, is essential for the smooth operation of hybrid teaching because it, for example, addresses technical challenges and facilitates effective communication. Overall, this study emphasizes the necessity of constructing a novel Bourdieu framework that can explain the socioeconomic factors that influence the interactions between the teaching and learning fields in the context of higher engineering education. By identifying key factors contributing to the positive perception of hybrid teaching, this research provides valuable insights that educators and institutions can use to optimize their hybrid teaching practices.